DO FİNANCİAL RATİOS AFFECT FIRM PRODUCTIVITY? AN EMPIRICAL ANALYSIS OF AUTOMOTIVE COMPANIES IN ASIAN PACIFIC (Third Sector Social Economic Review, 2024)
The main motivation for writing this study is to reveal the possible effects of the financial structures of automotive companies in the Asia-Pacific region on their productivity and to offer suggestions to company managers based on this. An empirical analysis is carried out using the data of 61 automotive companies operating in the Asia Pacific region for the period 2015:06-2021:06. The two-stage panel data analysis method, which is often used in the literature for measuring productivity and where errors are used as dependent variables, has been preferred. As a result of the estimation, it has been determined that the liquidity ratios and activity ratios of the companies have a positive impact on the productivity of the company. It has been found that the leverage ratio reflects negatively on productivity from financial structure ratios, while the effect of financial annuity and current asset annuity on productivity from profitability ratios is strong and positive. The two-stage panel data method preferred at the stage of productivity measurement was applied on a different sector and sample from previous studies, and the relationship between the financial indicators of companies and their productivity was examined.
Keywords: Productivity; Financial Ratios; Automotive; Asia-Pacific; Panel Data Analysis.